Strength Properties of Hardened Concrete Produced with Natural Aggregates for Different Water/Cement Ratios - Tugrul, Esra (My University, 2018)
Due to the competition in the concrete sector, there is a need for better quality and low-cost concrete production in recentyears. One of the changes that can be made in this direction is the use of natural aggregates, which are expected to beparticularly strong and obtained from river beds, in the production of concrete. It is intended to provide economic gain inTurkey, a country which is rich in terms of riverbeds, by evaluating these natural aggregates in the concrete production. Itis common to use crushed stones as aggregates in concrete. However, such aggregates are difficult and costly to manufacture.Therefore, it is necessary to evaluate the existing natural resources efficiently. This study aims to investigate the effects ofnatural aggregates on hardened concrete properties. In the present study, quartzitic natural aggregates from the river beds inthe Mediterranean region were used as aggregate. The experiments were carried out for different water/cement ratios bykeeping the aggregate granulometry and cement dosage constant. A number of concrete samples produced within the scopeof this study were subjected to hardened concrete tests such as compressive strength and splitting tensile strength. The resultsobtained are in accordance with the relevant TS standards. Thus, it was determined that these aggregates could be used inconcrete for concrete strength. The strength of concrete samples and water/cement ratio were determined to be inverselyproportional. In addition, a good fit was achieved between the results obtained from the compressive strength and splittingtensile strength tests.
Keywords: İnşaat Mühendisliği